Is nurses' clinical competence associated with their compassion satisfaction, burnout and secondary traumatic stress? A cross‐sectional study - Mohammad Ali Zakeri; Gholamreza Bazmandegan; Hamid Ganjeh; Maryam Zakeri; Sekineh Mollaahmadi; Ali Anbariyan; Zahra Kamiab (Wiley, 2021)
Abstract Aim The current study aimed to investigate the relationship between clinical competence and subscale of professional quality of life (ProQOL). Methods This cross‐sectional study was conducted from November 2018 to May 2019 on 291 nurses working in public hospitals in south Iran (Rafsanjan). The nurses were selected by convenience sampling method. Data were collected using the ProQOL questionnaire that included three subscales: compassion satisfaction, secondary traumatic stress and burnout and the Competency Inventory for Registered Nurse (CIRN) that measured clinical competence. Results A significant positive relationship was observed between compassion satisfaction and clinical competence. A significant negative association was found between compassion satisfaction and secondary traumatic stress/burnout and also between secondary traumatic stress and clinical competence. The results of regression analysis indicated that compassion satisfaction was the best predictor of secondary traumatic stress (R2 = 65%), burnout (R2 = 40%) and clinical competence (R2 = 12%). Moreover, secondary traumatic stress was found to be the best predictor of compassion satisfaction (R2 = 53%).